ADCP current measurements (38 and 75 kHz) during Maria S. Merian cruise MSM89 - Johannes Karstensen; Gerd Krahmann (PANGAEA, 2023)
Two Teledyne RDI Ocean Surveyor systems with 38 and 75 kHz transmission frequency were used. Data was processed with a software package developed at GEOMAR following the GO-SHIP standards (Firing and Hummon, 2010). The data was subsequently averaged over one minute intervals and converted to a NetCDF based format.